2021
DOI: 10.48550/arxiv.2102.01999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precise radial velocities of giant stars XV. Mysterious nearly periodic radial velocity variations in the eccentric binary $ε$ Cygni

Paul Heeren,
Sabine Reffert,
Trifon Trifonov
et al.

Abstract: Context. Using the Hamilton Échelle Spectrograph at Lick Observatory, we have obtained precise radial velocities (RVs) of a sample of 373 G-and K-giant stars over more than 12 years, leading to the discovery of several single and multiple planetary systems. The RVs of the long-period (∼ 53 years) spectroscopic binary ε Cyg (HIP 102488) are found to exhibit additional regular variations with a much shorter period (∼ 291 days). Aims. We intend to improve the orbital solution of the ε Cyg system and attempt to id… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…We notice this period is close to our detection of near 300-day periods. Importantly, the main star Cyg A (K0 III, 1.1M ) shows similar stellar properties (Heeren et al 2021) to our targets. In their work, they ruled out planetary hypothesis by detection of apparently time-varying RV amplitude and orbital period, and failure in orbital stability analysis.…”
Section: Long Secondary Periods In Giant Starssupporting
confidence: 70%
See 2 more Smart Citations
“…We notice this period is close to our detection of near 300-day periods. Importantly, the main star Cyg A (K0 III, 1.1M ) shows similar stellar properties (Heeren et al 2021) to our targets. In their work, they ruled out planetary hypothesis by detection of apparently time-varying RV amplitude and orbital period, and failure in orbital stability analysis.…”
Section: Long Secondary Periods In Giant Starssupporting
confidence: 70%
“…Nonetheless, in an up-to-date research, Heeren et al (2021) showed additional regular variations with a period of 291 days in the spectroscopic binary Cyg. We notice this period is close to our detection of near 300-day periods.…”
Section: Long Secondary Periods In Giant Starsmentioning
confidence: 91%
See 1 more Smart Citation